General Search Market Equilibrium - James W. Albrecht; Bo Axell (The Research Institute of Industrial Economics (IUI), 1982)
In this paper we extend models of search market equilibrium to incorporate general equilibrium considerations. The model we treat is one with a single product market and a single labor market. Imperfectly informed individuals follow optimal strategies in searching for a suitably low price and high wage. For any distribution of price and wage offers across firms these optimal strategies generate product demand and labor supply schedules. Firms then choose prices and wages to maximize expected profits taking these schedules as given, and the resulting profits are paid out to individuals as dividends. An equilibrium distribution of prices and wages is one which results from optimal price and wage setting behavior by firms given individuals optimal search strategies. There are two possible equilibrium configurations, a degenerate equilibrium in which all firms charge the same price and wage and a price and wage dispersion equilibrium. We show that there exists a degenerate equilibrium at the monopoly-monopsony price-wage combination. We also show some of the properties of a price-wage dispersion equilibrium, conditional on existence.
Keywords: D40; D50; 330; General equilibrium; Singel product and labor market; Consumers; Firms